Assessment of running speed at predicted maximal heart rate (vHRmax.pred) in trained runners - Yamaji, K.; Iguchi, F.; Hashizume, K. (Advances in Exercise and Sports Physiology, 2008)
Purpose: The purpose of the present study was to verify whether vHRmax.pred (a running speed corresponding toa HRmax predicted by the formula [220-age(yrs) was a useful index of endurance performance. vHRmax.pred was comapared with Vo2max, vV o2max (maximal aerobic running speed), vOBLA (running speed at a blood lactate level of 4mmol-1) and running speed at exhaustion in 20 male master runners(46-70yrs), twelve young male runners (21-31yrs) and 25 junior male runners (12-18 yrs). Methods: Physiological responses (V o2,HR and LT) were measured during progressive sub-maximal and maximal treadmill running. Running speeds corresponding to HRmax.pred,Vo2max and OBLA were estimated from regression relating the individua fsrunning speed to Vo2, HR, and LA, respectively. Results: A statistically significant correlation(p 0.05) was admitted between vHRmax.pred and Vo2max, vVo2max, vOBLA, RVE (running speed at the exhaustion or termination point) for the three groups and all participants, except between vHRmax.pred and relative Vo2max for young runners, and relative Vo2max and vOBLA for junior runners. Conclusion: It was suggested that vHRmax.pred was a potential index of endurance performance regardless of age.